Mitigation strategies for Li-ion battery thermal runaway: A review. (October 2021) - Xu, Bin; Lee, Jinwoo; Kwon, Daeil; Kong, Lingxi; Pecht, Michael
Abstract: Li-ion batteries are commercially successful power sources for diverse applications. However, the characteristics of Li-ion batteries make them susceptible to thermal runaway, resulting in fires and explosions. To mitigate safety hazards prior to the occurrence of thermal runaway, various strategies have been applied for battery cells, as well as battery packages. This article reviews safety strategies for Li-ion batteries, including positive temperature coefficient thermistors, positive temperature coefficient electrodes, current interrupt devices, safety vents, protection circuitry, shutdown separators, electrolyte additives, safe electrolytes, passive protection designs in battery packages, and battery management systems. The trigger conditions, protection mechanisms, drawbacks, and applications of representative strategies are discussed, and potential future risk mitigation approaches are explored. Highlights: An overview is given on safety hazards in Li-ion batteries. The thermal runaway process of Li-ion batteries is explained. Representative safety strategies at the cell level and the package level are reviewed. Pros and cons of reviewed safety strategies are summarized. The challenges and future risk mitigation trends in the battery industry are discussed.